2015
DOI: 10.1111/risa.12330
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception and the Public Acceptance of Drones

Abstract: Unmanned aircraft, or drones, are a rapidly emerging sector of the aviation industry. There has been limited substantive research, however, into the public perception and acceptance of drones. This article presents the results from two surveys of the Australian public designed to investigate (1) whether the public perceive drones to be riskier than existing manned aviation, (2) whether the terminology used to describe the technology influences public perception, and (3) what the broader concerns are that may i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
108
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(116 citation statements)
references
References 21 publications
7
108
0
1
Order By: Relevance
“…Of the 31 factors, perceived risk was the most frequently occurring variable and the one that was investigated the most in those studies. Clothier, Greer, Greer and Mehta (2015) and La Porte and Metlay (1975a) also agree on the significance of perceived risk when compared to other factors. Dobbie and Brown (2014) echo the sentiment that perceived risk is a hindrance in technology acceptance.…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…Of the 31 factors, perceived risk was the most frequently occurring variable and the one that was investigated the most in those studies. Clothier, Greer, Greer and Mehta (2015) and La Porte and Metlay (1975a) also agree on the significance of perceived risk when compared to other factors. Dobbie and Brown (2014) echo the sentiment that perceived risk is a hindrance in technology acceptance.…”
mentioning
confidence: 75%
“…Also, terminology presented in one location may not be appropriate in another (Petts et al, 2002). Interestingly, Clothier et al (2015) contrarily found no link between terminology and perceived risk. Simply presenting media in the wrong context can also present problems.…”
Section: Media Communicationmentioning
confidence: 92%
See 3 more Smart Citations